IMPROVING STUDENTS’ READING COMPREHENSION THROUGH QUESTION ANSWER RELATIONSHIP STRATEGY (QARS) - Ade Sahbana Damanik; Herman Herman (INOVISH JOURNAL, 2021)
This research was intended to find out the empirical evidence of the influence the (QARS) Question Answer Relationship strategy on student reading comprehension ability in reading comprehension explanation text. The research used quantitative method with quasi experimental design This research was used purposive sampling with the research sample totally 20 students with classified into two classes, namely experimental group and control group, the population of this research was eight grade of SMP YPK Pematangsiantar. The instrument used is reading comprehension test, before giving treatment the student from both classes were give pre-test to know the ability of student reading comprehension in reading explanation text, the test consists 10 multiple choice question.at the end of treatment the student given post-test the data from both tests were analyzed by using mean to measure the score of student the result of mean score of pre-test reveal a significant improvement between pre-test and post-test. In the pre-test the experimental group got 61 while the control group 66 in post-test